KEWENANGAN PIMPINAN PARTAI POLITIK DALAM PENGUSULAN PEMBERHENTIAN ANGGOTA DPR TERKAIT TINDAK PIDANA KORUPSI - Budiyanto, Bambang (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2017)
Political parties have a strategic role in a democratic country. Indonesian 1945 Constitution regulates the status of political parties in the state life in Indonesia. Political parties are the only organization that can become participants in the elections and nominate candidates to fill political positions. One of the authorities of political parties is to nominate candidates of legislators both at the central and regional levels. In addition to nominating candidates for members of Parliament, political parties also have the authority to dismiss members of political parties in the Parliament. Departing from this issue, this study discusses two main problems related to the authority of political parties against the dismissal of the members of the House of Representatives in Indonesia as well as on construction of the arrangements for the provision of dismissal of members of parliament tied to corruption . This research was conducted with the use of normative legal research conducted through an analysis of the norms of the legislation. The study results show that political parties have a very important role in democracy and running the country. In addition to the authority of nominating candidates to fill political positions in the executive and legislative, political parties are also given the authority to replacement and dismissal of members of the House of Representatives. Related to the dismissal of members of the party sitting in Parliament, the political parties should set very important conditions such as the problem of corruption. This serves as a precautionary measure and efforts to realize corruption-free state officials, because corruption has a very serious impact on the life of the nation. Thus the judicial review provided for in Article 16 of Law No. 2 of 2011 concerning the Amendment Act No. 2 of 2008 on Political Parties needs to be done, and then revised. This is to fill the void of legal norms tied to provisions of the dismissal of members of political parties in the House of Representatives due to corruption. Partai politik mempunyai peran strategis dalam negara demokrasi. UUD NRI 1945 telah mengatur kedudukan partai politik dalam kehidupan bernegara di Indonesia. Partai politik adalah satu-satunya organisasi yang dapat menjadi peserta pemilu dan mengajukan calon untuk mengisi jabatan-jabatan politik. Salah satu kewenangan partai politik adalah mengajukan calon anggota DPR baik di pusat maupun di daerah. Selain mengajukan calon anggota DPR, partai politik berwenang memberhentikan anggota partai politik yang duduk di DPR. Bertolak dari hal tersebut, penelitian ini membahas dua pokok permasalahan yaitu yang berkaitan kewenangan pimpinan partai politik dalam mengusulkan pemberhentian anggota DPR terkait tindak pidana korupsi serta tentang konstruksi pengaturan  terhadap ketentuan pemberhentian anggota DPR terkait tindak pidana korupsi. Penelitian ini dilaksanakan dengan menggunakan penelitian hukum normatif yang dilakukan melalui analisis terhadap norma dalam peraturan perundang-undangan. Berdasarkan hasil penelitian ini bahwa partai politik mempunyai peran sangat penting dalam demokrasi dan penyelenggaaraan negara. Selain diberikan kewenangan untuk mengajukan calon-calon untuk mengisi jabatan-jabatan politik di eksekutif dan legislatif, partai politik juga diberikan kewenangan untuk melakukan pergantian dan pemberhentian anggota DPR. Terkait dengan pemberhentian anggota partai yang duduk di DPR seharusnya mengatur ketentuan yang sangat penting seperti masalah korupsi. Hal ini sebagai langkah pencegahan dan dalam upaya mewujudkan penyelenggara negara yang bebas KKN, sebab korupsi mempunyai dampak sangat serius dalam kehidupan berbangsa dan bernegara. Dengan demikian judicial review dalam ketentuan Pasal 16 UU No. 2 Tahun 2011 tentang Perubahan Atas Undang-Undang Nomor 2 Tahun 2008 tentang Partai Politik perlu dilakukan, yang selanjutnya dilakukan direvisi. Hal ini untuk mengisi kekosongan norma hukum terkait ketentuan pemberhentian anggota partai politik di DPR yang disebabkan tindak pidana korupsi.
Keywords: Authority; Political Party; House of Representatives; Corruption; Kewenangan; Partai Politik; Dewan Perwakilan Rakyat; Tindak Pidana Korupsi